Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1258/jtt.2012.sft111
|View full text |Cite
|
Sign up to set email alerts
|

A review of Medicare expenditure in Australia for psychiatric consultations delivered in person and via videoconference

Abstract: We examined the activity (services recorded) and cost (benefits paid) of reimbursement associated with telepsychiatry services in the Australian public health-care sector. We reviewed the activity and costs administered through the government's Medicare Benefits Schedule (MBS) from July 2002 to June 2011. During this nine-year-period, almost 14 million psychiatric consultations were funded through Medicare at a cost of $1.6 billion. Of these, 8003 were telepsychiatry consultations which cost $934,000, i.e. the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…One of the simplest assessments of cost data compares the collection of direct and indirect costs associated with patient encounters in telepsychiatry and FTF psychiatry visits. Studies that assessed the cost effectiveness of telepsychiatry have evaluated the direct costs of provider time [98] , medical supplies [96] , technology [53] , and reimbursement [99] .…”
Section: Cost-effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the simplest assessments of cost data compares the collection of direct and indirect costs associated with patient encounters in telepsychiatry and FTF psychiatry visits. Studies that assessed the cost effectiveness of telepsychiatry have evaluated the direct costs of provider time [98] , medical supplies [96] , technology [53] , and reimbursement [99] .…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…The literature reviewed suggests that telepsychiatry may have greater up-front costs associated with service delivery when compared to FTF; however, there appears to be "tipping points" at which telepsychiatry begins to eclipse the cost-effectiveness of FTF interventions. Several studies identified the number of consultations at which telepsychiatry became more cost effective than FTF, with the number of consultations delivered ranging from 131 [99] to 249 [98,100] to 379 [103] . For example, Butler et al [98] found that the cost savings of telepsychiatry occur after the health center or provider delivers 249 consultations.…”
Section: Assessment Of Direct and Indirect Costsmentioning
confidence: 99%
“…The opportunities afforded by telehealth were widely recognised by participants, particularly in view of changes in the Medical Benefits Schedule [32]. Technological solutions could be used for a range of purposes such as case conferencing with patient's families, and diagnostic and clinical management.…”
Section: Telehealthmentioning
confidence: 99%
“…In Australia, one statewide health department has demonstrated that telehealth can successfully provide emergency mental health care for rural communities [9]. There has been significant progress in developing funding models to accommodate changes to clinical practice caused by telehealth by reimbursements for time and subsidies for infrastructure setup for providers [10,11]. In the US there has been a "spike in interest" and use of telehealth following recent changes to legislation which provides guaranteed payment for providing telehealth services and the anticipated implementation of the Affordable Care Act [6].…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, only 0.06% of the 14 million psychiatric consultations carried out between July 2002 and June 2011 were through telehealth [11]. This increased to only 1.46% between July 2011 and April 2014 [13].…”
Section: Introductionmentioning
confidence: 99%